Combinatorial MD/QM studies to develop novel ionic liquid-based anticancer drug delivery systems with aminium derived from carbohydrates as cationic components - Sepideh Kalhor; Alireza Fattahi (Scientific Reports)
Abstract The main challenges in anticancer drug design include solubility in organic and aqueous phases, bioavailability, selective targeting of specific receptors, and low toxicity. Notably, solubility, bioavailability, and receptor-specific targeting are interconnected factors that significantly influence the therapeutic efficacy of anticancer drugs. The primary objective of this study is to design novel drug delivery systems based on ionic liquids. These systems incorporate structures such as N, N, N-trimethyl-2-(((2 S,3R,4 S,5 S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)tetrahydro-2 H-pyran-2-yl)oxy)ethan-1-aminium (GTA) and (2 S,3R,4 S,5 S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)-N, N, N-trimethyltetrahydro-2 H-pyran-2-aminium (NTPA) derived from carbohydrates as cationic components, with anticancer drugs acting as anions. The goal is to investigate the effects of these novel pharmaceutical active ionic liquids on the interactions between the drugs and cell membranes. Additionally, this study examines changes in the solubility of anticancer drugs in both organic and aqueous phases after their conversion into ionic liquids. Molecular dynamics simulations (MD) and quantum mechanics calculations (QM) are employed to achieve these objectives. Known anticancer-candidate ionic liquid, such as 3-(2-((4-fluorophenyl)amino)-2-oxoethyl)-1-methyl-1 H-imidazol-3-ium-tetrafluoroborate, is considered as a reference point in our investigations. Furthermore, we aim to assess whether the direct attachment of the aminium group to the saccharide portion of the cations or the indirect attachment through a choline group significantly impacts the final properties of the designed anticancer ionic liquids. Another aim of this study is to demonstrate that QM studies need to be complemented by MD studies to provide insights into the behaviors of ionic liquids. Initially, we calculate the binding energies between cations and anions of all the ionic liquids at the B3LYP/6-311 + + G(d, p) level of theory. Subsequently, molecular dynamics simulations using GROMACS 5.2 are employed to obtain more precise information about these understudied ionic liquids. A combination of density functional theory (DFT) calculations and a solvation model based on density (SMD) is utilized to determine the solubility of free anticancer drugs and our active anticancer ionic liquids in various phases. We validate our findings by evaluating the interactions between the formulated ionic liquids and cell membranes using the DPPC model through combined MD simulations and docking procedures.